The electrical resistivity method of geophysical prospecting and its practical application to geological problems of economic importance in the Union of South Africa - Enslin, J. F.(Johan Frederik) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc. Physics) -- University of Stellenbosch, 1944.